Sex‐ and Race‐Related Differences in Characteristics and Outcomes of Hospitalizations for Heart Failure With Preserved Ejection Fraction. Issue 4 (April 2017) - Goyal, Parag; Paul, Tracy; Almarzooq, Zaid I.; Peterson, Janey C.; Krishnan, Udhay; Swaminathan, Rajesh V.; Feldman, Dmitriy N.; Wells, Martin T.; Karas, Maria G.; Sobol, Irina; Maurer, Mathew S.; Horn, Evelyn M.; et al.
Abstract : Background: Sex and race have emerged as important contributors to the phenotypic heterogeneity of heart failure with preserved ejection fraction (HFpEF). However, there remains a need to identify important sex‐ and race‐related differences in characteristics and outcomes using a nationally representative cohort. Methods and Results: Data were obtained from the Agency for Healthcare Research and Quality Healthcare Cost and Utilization Project—Nationwide Inpatient Sample files between 2008 and 2012. Hospitalizations with a diagnosis of HFpEF were included for analysis. Demographics, hospital characteristics, and age‐adjusted comorbidity prevalence rates were compared between men and women and whites and blacks. In‐hospital mortality was determined and compared for each subgroup. Multivariable regression analyses were used to identify and compare correlates of in‐hospital mortality for each subgroup. A sample of 1 889 608 hospitalizations was analyzed. Men with HFpEF were slightly younger than women with HFpEF and had a higher Elixhauser comorbidity score. Men experienced higher in‐hospital mortality compared with women, a finding that was attenuated after adjusting for comorbidity. Blacks with HFpEF were younger than whites with HFpEF, with lower rates of most comorbidities. Hypertension, diabetes, anemia, and chronic renal failure were more common among blacks. Blacks experienced lower in‐hospital mortality compared with whites, even after adjusting for age and comorbidity. Important correlates of mortality among all 4 subgroups included pulmonary circulation disorders, liver disease, and chronic renal failure. Atrial fibrillation was an important correlate of mortality only among women and blacks. Conclusions: Differences in patient characteristics and outcomes reinforce the notion that sex and race contribute to the phenotypic heterogeneity of HFpEF.